Trzy teologie polityczne Carla Schmitta - Buksiński, Tadeusz (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
The article refers exclusively to the Carl Schmitt’s political theology. His three conceptions of political theology and corresponding theoretical approaches are reconstructed and precisely analysed. The first conception is called the sociology of concepts or the theory of analogies between religious and legal-political concepts. The second Schmitt’s approach to political theology is the eschatological conception. Both these conceptions are basically descriptive and analytical. Solely the third conception is normative (and political), therefore, its presents the concept of political theology as a normative approach to the Political.